Expansion of local geographic and host ranges of Nipaecoccus nipae (Mskell) (Pseudococcidae, Hemiptera) in the Philippines with new records of predators and attending ants (The Philippine Journal of Crop Science, 2012)
The local geographical distribution of the buff coconut mealybug (BCM), Nipaecoccus nipae (Maskell) (Pseudococcidae, Hemiptera) has widened since its initial invasion of Luzon Island in the early 2000s, being now known to occur in other islands and provinces in the Philippines. Surveys were conducted in several regions by initially inspecting known hosts of BCM and other plants. Samples of BCM and of host plants were collected, the latter identified to species. Seventeen (17) plant species belonging to 12 families are recorded as new hosts of BCM, bringing its total known host plants in the Philippines to 71 species in 20 families. An updated host list was prepared to include all local plants that serve as hosts of this invasive species. New associated organisms are also reported for the first time. These include larvae of the green lacewing, Mallada basalis (Walker) (Chrysopidae, Neuroptera) and the brown lacewing. Micromus igorotus Banks (Hemerobiidae, Neuroptera) that have been observed to prey on nymphs and adults, the first known locally available natural enemies of BCM. The black ants, Dolichoderus thoracicus (Smith), fire ants, Solenopsis geminata (Jerdon), and crazy ants, anoplolepis gracilipes (Fabricius) (Formicidae, Hymenoptera), are also now occasionally observed to attend to BCM colonies.